Curriculum design from theory to practice: preparing Japanese students to study abroad using content‐based language teaching. Issue 2 (11th June 2020) - Miller, Lisa R.; Klassen, Kimberly; Hardy, Jacques W.
Abstract : This paper documents the design, implementation and evaluation of a content‐based language teaching (CBLT) curriculum for an English for Academic Purposes (EAP) programme at a Japanese university. The aim of the programme is to prepare students for study abroad in Anglophone universities in a two‐year time frame. This curriculum redesign project integrated second language learning theory with backward design curriculum development theory in an institutional setting where administration mandates and changing student and faculty populations impacted the process. The curriculum team conducted a needs analysis with multiple data sources, implemented the curriculum, and then, conducted an evaluation utilising various sources. The needs analysis revealed several surprises, countering faculty and curriculum designers' intuition. Likewise, conflicting student and faculty feedback in the evaluation of the curriculum posed difficulties for drawing conclusions about the curriculum's effectiveness. The university context, with its emphasis on academic freedom and research, requires adjusting theoretically based processes used in compulsory education levels, such as adopting an adaptable approach to curriculum design. As more universities require faculty to write and revise curricula, the authors call for more tertiary‐level curriculum design case studies that illustrate successes or shortcomings for curriculum design theory in the face of real‐world challenges.